Emotion the science of sentiment - Evans, Dylan 1966- (Oxford Univ. Press, 2001)
Was love invented by European poets in the middle ages, as C.S. Lewis claimed, or is it part of human nature? Will winning the lottery really make you happy? Is it possible to build robots that have feelings? These are just some of the intriguing questions explored in this new guide to the latest thinking about emotions. Drawing on a wide range of scientific research, from anthropology and psychology to neuroscience and artificial intelligence, Emotion : the science of sentiment takes the reader on a fascinating journey into the human heart. Illustrating his points with entertaining examples from fiction, film, and popular culture, Dylan Evans ranges from the evolution of emotions to the nature of love and happiness to the language of feelings, offering readers the most recent thinking on real life topics that touch us all.